Síntese e investigações estruturais de arranjos supramoleculares formados por metaloporfirinas e metaloftalocianinas - Melo, Cristiane Cabral de (Universidade Federal de São Carlos, 2012)
This thesis involves the syntheses and characterization of four heterotriads formed by metallotetraphenylporphyrins (CoTPP and NiTPP) and metallophthalocyanines (CoPc and NiPc) using pyrazine (pz) and trans-1,2-bis(4-pyridyl)ethylene (bpe) as spacer ligands. The following sequences: NiPc(pz)CoTPP(pz)NiPc, NiTPP(pz)CoPc(pz)NiTPP, NiTPP(bpe)CoPc(bpe)NiTPP and CoTPP(bpe)CoPc(bpe)CoTPP were investigated. All triads were analyzed by infrared and ultraviolet-visible spectroscopy and some of them were characterized by elemental analysis, termogravimetry and differential thermal analysis. The infrared and electronic spectra of the triads showed characteristic absorption bands of the two macrocycles. The elemental data are in a good agreement with the proposed stoichiometry of these arrays. The triad NiTPP(pz)CoPc(pz)NiTPP had its stoichiometry confirmed via thermogravimetry and elemental analysis. Besides these results, this thesis also reports the crystal structure of a new pseudopolymorph of cobalt tetraphenylporphyrin (CoTPP) obtained by single-crystal X-ray diffraction. This non-stoichiometric solvate crystallized in the space group Pī with unit cell parameters distinct from the non-solvated CoTPP, which in general, like others metallotetraphenylporphyrins, tends to crystallize in the tetragonal space group I42d. The triclinic and tetragonal forms differ with respect to the conformation adopted by the macrocycle and also in the phenyl orientation. Crystal packing analysis of this pseudopolymorph revealed the presence of infinite channels along the a axis that are filled by dichloromethane solvent molecules, which represents therefore the first clathrate of CoTPP reported in the literature.
Syntheses and structural investigations of supramolecular arrays formed by metalloporphyrins and metallophthalocyanines
Keywords: Química inorgânica; Síntese; Arranjos supramoleculares mistos; Metaloporfirinas; Metaloftalocianina; Clatrato; Metallotetraphenylporphyrins; Metallophthalocyanines; Mixed tetrapirrolic arrays; Clathrate; CIENCIAS EXATAS E DA TERRA::QUIMICA